Identification and functional characterization of a flavonol synthase gene from sweet potato [Ipomoea batatas (L.) Lam.] - Kou, Meng; Li, Chen; Song, Weihan; Shen, Yifan; Tang, Wei; Zhang, Yungang; Wang, Xin; Yan, Hui; Gao, Runfei; Ahmad, Muhammad Qadir; Li, Qiang (Frontiers in Plant Science, 2023)
Flavonol synthase (FLS) is a key enzyme of the flavonoid biosynthetic pathway, which catalyzes dihydroflavonols into flavonols. In this study, a FLS gene was cloned and characterized from sweetpotato and designated IbFLS. The deduced IbFLS protein showed high identities with other plant FLSs. The conserved amino acids (HxDxnH motifs) binding ferrous iron and residues (RxS motifs) binding 2-oxoglutarate were found in IbFLS at conserved positions like other FLSs, suggesting that IbFLS belongs to the 2-oxoglutarate-dependent dioxygenases (2-ODD) superfamily. qRT-PCR analysis showed that there was an organ-specific expression pattern by the IbFLS gene and it was predominantly expressed in young leaves. The recombinant IbFLS protein could catalyze the conversion of dihydrokaempferol and dihydroquercetin to corresponding kaempferol and quercetin respectively. Subcellular localization result indicated that IbFLS was targeted to nuclear and cytomembrane. Furthermore, silening of IbFLS in sweetpotato altered leaves colour into purple, substantially inhibiting the expression of IbFLS and upregulating the expression of genes involved in the downstream pathway of anthocyanin biosynthesis (i.e., DFR, ANS and UFGT). The total anthocyanin content in the leaves of the transgenic plants was dramatically increased, whereas the total flavonol content was significantly reduced. Thus, we conclude that IbFLS plays critical roles in the flavonol biosynthetic pathway and is potentially a key point of genetic engineering toward colour modification in sweetpotato.